Some Characterizations of Osculating Curves in the Lightlike Cone - Kulahci, Mihriban; Almaz, Fatma (Soc Paranaense Matematica, 2017)
In this paper, we give the first kind and second kind osculating curves in the lightlike cone. In addition we characterize osculating curves in terms of their curvature functions.
Keywords: Osculating curve; lightlike cone